UPAYA PENINGKATAN PROFESIONALITAS GADIK AKMIL GUNA MENDUKUNG PEMBELAJARAN DI AKADEMI MILITER MAGELANG - Ariani, Diah Novita; Widiastuti, Nur (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
The objectives to be achieved in writing this thesis are to find out the obstacles in the professional development of Gadik Akmil to support learning at the Military Academy and to formulate efforts to improve the professionalism of Gadik Akmil to support learning at the Military Academy.This research is a qualitative, descriptive research supported by data obtained through observation, interviews and involvement with the research object. The qualitative analysis model uses the Miles & Hubberman model. Constraints in improving the professionalism of Gadik Akmil to support learning at the Magelang Military Academy include (1) In the field of education the obstacle is that there are still Gadik who have not been educated according to the provisions so that learning activities become less than optimal, the Magelang Military Academy curriculum that applies at this time is felt to have to continue to adapt to global challenges, the condition of hardware and software at the Magelang Military Academy needs to be updated, the weak level of coordination and integration between institutions responsible for education, the influence of globalization is unavoidable, the limited institutional financial budget, (2) the field of research is constrained by the limited opportunity to submit proposals that can be approved, (3) The field of community service is constrained by cultural diversity from the local community or implementers, lack of consistency, evaluation and feedback from program implementers. Efforts to increase the professionalism of Gadik Akmil to support learning at the Magelang Military Academy include (1) increasing the motivation of Magelang Akmil girls/lecturers in the implementation of the Integrated Tridharma, (2) increasing the integration of the implementation of the Tridharma with the output of higher education goals both integration of education with research, integration education with community service as well as integration of research with community service, (3) Increasing Monitoring and Evaluation of the Implementation of the Tridharma. Tujuan yang ingin dicapai dalam penulisan tesis ini adalah untuk mengetahui kendala dalam peningkatan profesional Gadik Akmil guna mendukung pembelajaran di Akademi Militer dan untuk merumuskan upaya peningkatan profesional Gadik Akmil guna mendukung pembelajaran di Akademi Militer. Penelitian ini adalah penelitian kualitatif, deskriptif didukung dengan data yang diperoleh melalui observasi, wawancara dan keterlibatan dengan objek penelitian. Model analisis kualitatif menggunakan model Miles & Hubberman. Kendala dalam peningkatan profesional Gadik Akmil guna mendukung pembelajaran di Akademi Militer Magelang antara lain (1) Bidang pendidikan kendalanya masih ada Gadik yang belum berpendidikan sesuai dengan ketentuan sehingga kegiatan pembelajaran menjadi kurang optimal, kurikulum Akmil Magelang yang berlaku pada saat ini dirasa harus terus beradaptasi dengan tantangan global, kondisi perangkat keras dan lunak di Akmil Magelang perlu diperbaharui, lemahnya tingkat koordinasi dan keterpaduan antar lembaga yang bertanggung jawab dalam dunia pendidikan, pengaruh globalisasi yang tidak dapat dihindarkan, Terbatasnya anggaran keuangan institusi, (2) Bidang penelitian kendalanya keterbatasan memperoleh kesempatan mengajukan proposal yang dapat disetujui, (3) Bidang pengabdian pada masyarakat kendalanya keragaman budaya dari masyarakat setempat ataupun para pelaksana, kurangnya konsistensi, evaluasi dan umpan balik dari pelaksana program.Upaya peningkatan profesional Gadik Akmil guna mendukung pembelajaran di Akademi Militer Magelang antara lain dengan (1) meningkatkan motivasi gadik/dosen Akmil Magelang dalam pelaksanaan Tridharma Terpadu, (2) meningkatkan integrasi pelaksanaan Tridharma dengan output tujuan pendidikan perguruan tinggi baik integrasi pendidikan dengan penelitian, integrasi pendidikan dengan pengabdian masyarakat serta integrasi penelitian dengan pengabdian masyarakat, (3) Lebih meningkatkan Monitoring Dan Evaluasi Pelaksanaan Tridharma.